2022
DOI: 10.1002/lsm.23596
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term improvement in the appearance of hypertrophic scars following a single treatment with acoustic subcision—A single center proof‐of‐concept study

Abstract: Introduction and Objectives Fibrosis, including hypertrophic scar formation, is a pathological condition characterized by excessive production and accumulation of collagen, and loss of tissue architecture, in response to wound healing. Alterations in the extracellular matrix (ECM) biomechanical properties may be important in modulating myofibroblasts and fibrosis formation. The acoustic subcision device uses rapid acoustic pulse technology to noninvasively improve the appearance of hypertrophic scars through b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Macrophage‐secreted TGF‐β contributes to fibroblast activation, which causes scarring and contractures 57,58 . Unsurprisingly, all of the burn patients in this study had measured scar thickness of more than 3 mm, all showed delayed healing, and all had repeated burn procedures; these are all predictors of hypertrophic scarring 59,60 . MIP‐1 is a macrophage and monocyte chemoattractant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Macrophage‐secreted TGF‐β contributes to fibroblast activation, which causes scarring and contractures 57,58 . Unsurprisingly, all of the burn patients in this study had measured scar thickness of more than 3 mm, all showed delayed healing, and all had repeated burn procedures; these are all predictors of hypertrophic scarring 59,60 . MIP‐1 is a macrophage and monocyte chemoattractant.…”
Section: Discussionmentioning
confidence: 86%
“…57,58 Unsurprisingly, all of the burn patients in this study had measured scar thickness of more than 3 mm, all showed delayed healing, and all had repeated burn procedures; these are all predictors of hypertrophic scarring. 59,60 MIP-1 is a macrophage and monocyte chemoattractant. It has been shown that lower levels can reduce angiogenesis, macrophage recruitment, and contribute to delayed healing.…”
Section: Burn Injury Induces Changes In Effector T-cell Expression Of...mentioning
confidence: 99%
“…As MMP2 has been previously shown to degrade collagen as one of its substrates [33,34], and as collagen accumulation is associated with fibrosis in different tissues [35,36], we next asked whether the observed pathophysiology in the MMP2-nulls is coupled with accumulation of collagen in the uterine wall. Masson’s Trichrome staining for collagen fibrils was performed on transverse sections from nulliparous WT and mmp2 -/- uteri at 12M of age, demonstrating an increase in collagen fibrils in mmp2 -/- tissue as shown by the increased blue staining mostly in the circular myometrium layer, compared to WT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As MMP2 has been previously shown to degrade collagen as one of its substrates [33,34], and as collagen accumulation is associated with fibrosis in different tissues [35,36],…”
Section: Mmp2 -/Nulliparous Uterine At 12m Demonstrates Signs Of Myom...mentioning
confidence: 99%
“…Collagen accumulation in associated with fibrosis in several tissues, including the liver, kidney and uterus [32][33][34][35][36]. For example, Xu et al showed enhanced collagen expression and fibrosis in the mouse uterus, which are associated with Notch1 signaling [35].…”
Section: Mmp2 −/− Nulliparous Uterus At 8 M Demonstrates Signs Of Myo...mentioning
confidence: 99%